The Impact of High-Performance Work Systems on Employees: A Sectoral Comparison - Michael White; Alex Bryson (Institute of Labor Economics (IZA), 2019)
Using nationally representative linked employer-employee surveys of workplaces with 50 or more employees we find the adoption of High-Performance Work Systems (HPWS) in the private sector is largely positively correlated with employee job attitudes pre-recession. However, high intensity HPWS has partly adverse consequences for private sector employees in the post-recession period. In contrast, there are no indications of public sector employees responding positively or negatively to HPWS and HPWS is not associated with adverse effects post-recession. The sectoral difference in results is interpreted in terms of different employment relationships and different sources of employee motivation.
Keywords: I31; J45; M5; 330; high performance work systems; public sector; organizational commitment; intrinsic job satisfaction; well-being